2016
DOI: 10.1007/s11205-016-1376-4
|View full text |Cite
|
Sign up to set email alerts
|

Does Consumer Confidence Forecast Household Saving and Borrowing Behavior? Evidence for Poland

Abstract: Consumer confidence plays an important role in households’ decision-making processes. This study investigates the effects of consumer confidence on household saving and borrowing behavior that are unsatisfactorily considered in previous discussions. The questions of interest are first, whether indexes of consumer confidence have any predictive power on their own for future household saving and borrowing rates, and second, whether they contain information about future household saving and borrowing rates aside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 44 publications
3
27
0
Order By: Relevance
“…These results are in line with those obtained by Łyziak and Mackiewicz-Łyziak (2014) In the present study we also find evidence regarding the informative value of surveybased expectations. Our results are in line with recent findings by Altug and Çakmakli (2016), Klein and Özmucur (2010), Kłopocka (2017) and Lehmann and Wohlrabe (2017). Altug and Çakmakli (2016) found survey expectations useful to improve inflation forecasts.…”
Section: Sweden United Kingdomsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in line with those obtained by Łyziak and Mackiewicz-Łyziak (2014) In the present study we also find evidence regarding the informative value of surveybased expectations. Our results are in line with recent findings by Altug and Çakmakli (2016), Klein and Özmucur (2010), Kłopocka (2017) and Lehmann and Wohlrabe (2017). Altug and Çakmakli (2016) found survey expectations useful to improve inflation forecasts.…”
Section: Sweden United Kingdomsupporting
confidence: 93%
“…Klein and Özmucur (2010) found evidence that survey expectations improved the forecasting performance of autoregressive time series models in European countries. Kłopocka (2017) showed the usefulness of survey indicators to forecast household saving and borrowing rates in Poland. Lehmann and Wohlrabe (2017) found that consumers' unemployment expectations and new orders improved predictions of employment growth in Germany.…”
Section: Sweden United Kingdommentioning
confidence: 99%
“…The strong link between consumer confidence and savings are already recognized by some studies (e.g. Kłopocka 2016), so this finding is hardly a surprise.…”
Section: Resultsmentioning
confidence: 51%
“…CCI, also known as Index of Consumer Sentiment, is used to reflect the consumers' psychological feelings and confidence about economic situation and consumption at the moment or in a certain period of time (Islam & Mumtaz, ; Kłopocka, ), including consumer's views on various economic situations such as interest rate, employment, and price status. CCI includes the Index of Current Economics Condition (ICC) and Index of Consumer Expectations (ICE) (National Bureau of Statistics, ).…”
Section: Introductionmentioning
confidence: 99%
“…Research on consumer psychology showed that consumers' subjective confidence of economic condition would directly predict and influence macroeconomic condition, along with the concept of Consumer Confidence Index (CCI) emerging (Gholipour Fereidouni & Tajaddini, 2017;Li, Chang, & Chen, 2008;Sori c, 2018). CCI, also known as Index of Consumer Sentiment, is used to reflect the consumers' psychological feelings and confidence about economic situation and consumption at the moment or in a certain period of time (Islam & Mumtaz, 2016;Kłopocka, 2017) ICE represents the level of consumers' expectation of the economic condition and consumption over a period in the future, which reflects the confidence of future economic development.…”
Section: Introductionmentioning
confidence: 99%